Maintaining Hygiene in Orthodontic Miniscrews: Patient Management and Protocols-A Literature Review - Riccardo Favero; Martina Fabiane; Andrea Zuccon; Diego Conte; Francesco Saverio Ludovichetti (MDPI AG, 2024)
Background: Oral hygiene is crucial for the success of orthodontic therapy involving temporary anchoring devices like miniscrews. Plaque buildup, exacerbated by orthodontic appliances, causes inflammation that can undermine treatment outcomes. Individualized prevention plans based on patient risk factors are essential. This review emphasizes the importance of oral hygiene in orthodontic therapy with miniscrews, identifies optimal devices for ensuring long-term stability, and explores protocols for high-risk patients. Materials And Methods: A comprehensive search was conducted on two primary databases, PubMed and Google Scholar, for relevant articles on oral hygiene and inflammation. Fourteen articles meeting the inclusion criteria were selected, covering topics such as "orthodontic miniscrew", "miniscrew and laser", "miniscrew and mouthwash", "electric toothbrush", and "GBT". Results: Inflammation can compromise miniscrew stability by damaging surrounding bone. Miniscrews of 10 mm length have lower failure rates due to better bone contact and stability. Chlorhexidine reduces inflammation risk and inhibits epithelialization around the implant head. Laser therapy enhances miniscrew stability and reduces inflammation. Chitosan effectively suppresses inflammatory mediators and prevents microorganism adhesion. Both sonic and roto-oscillating electric toothbrushes remove plaque effectively, with roto-oscillating brushes showing superior results. The Guided Biofilm Therapy (GBT) protocol offers professional hygiene benefits similar to traditional methods, with improved patient engagement and motivation. Conclusions: Home oral hygiene maintenance is paramount for preventing inflammatory complications. Professional interventions such as diode laser usage, particularly in adult patients with a history of periodontitis or underlying systemic conditions, can mitigate orthodontic therapy failure risks. The GBT protocol fosters a more comfortable and participatory professional hygiene experience for patients, promoting better oral health awareness and compliance.